SOCIALLY ENGAGED VIETNAMESE BUDDHISM IN THE POSTCOLONIAL PERSPECTIVE - Kriaučiūnaitė, Kotryna (Politologija, 2017)
The aim of this article is to reveal the origin of the socially engaged Vietnamese Buddhism and the methods by which this religious practice operated within the society during the presidency of Ngo Dinh Diem. This article is based on the phenomenon of socially engaged Buddhism through the ideas of postcolonial discourse theorists. The resistance from colonialism through manifestations is an important moment in the history of each state that has regained its independence. This article develops the idea that the history of Vietnam’s independence and modernization is closely linked to the expression of socially engaged Buddhism, which made the resistance movement united and effective. The end of the Second World War, which marked the decline of colonialism and made it possible for Vietnam to become an independent state, in which the freedom of religion was guaranteed, was perceived differently in the southern region of the country. The Head of South Vietnam, Ngo Dinh Diem, widely known as a marionette of France and the US, is a politician who continued to repress Buddhists. During his presidency, Buddhism had gained a rather new, socially active form, which had mobilized the society – both the monks and the laypeople – and influenced it over the political situation in the country. The aim of this paper is to get acquainted with the phenomenon of socially oriented Buddhism in Vietnam, to understand the conditions that led to its emergence, and to reveal the methods by which this form of Buddhism opposed colonial manifestations in the postcolonial perspective. During the first years of the Vietnam War and the Ngo Dinh Diem regime, the non-political goal of socially engaged Buddhism was to protect the people from suffering; however, the Ngo Dinh Diem presidency was marked by the continuation of the colonial model, which encouraged Buddhists to become a visible political power. Although Buddhist protests were of extreme risk and had cost lives, these people, who had a purely religious freedom and incentive rights, became a movement that was characterized by a deeper, hidden goal – a struggle against the postcolonial policy that the US had exerted in Asian countries. Socially engaged Buddhism can be judged by its ability to adapt to existing social challenges. Although the defense of religious symbols and rights in Vietnam during the Diem years was the main objective, the further goals became politically motivated. They were linked to the liberation of a society from colonialism; thus, it can be argued that Vietnamese Buddhism, which began as a struggle for religious rights and later became a political ideology, also marked the process of modernizing a sovereign state. It has become a world-class movement with the aim to remove the spread of pro-Western ideas in Vietnam.